2019
DOI: 10.1111/joms.12540
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Proto‐Institutions in the New Normal Business Landscape: Dialectic Institutional Work and the Dutch Drone Industry

Abstract: In the current business landscape, in which technology‐enabled entrepreneurship is part of the New Normal, regulatory institutional structures are in constant flux. Previous studies have framed the challenges facing entrepreneurs in mature organizational fields as avoiding the power of overbearing regulators long enough to establish the legitimacy of their ventures. In fields typified by New Normal conditions, however, regulatory frameworks for evaluating new technology‐enabled ventures are often still lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Most IW research has been conducted in strong institutions, such as state bureaucracies (Goodstein & Velamuri, 2009;Xiao & Klarin, 2019). Weak institutions are less developed, such as proto-institutions and institutional voids (Gong & Hassink, 2019;Smolka & Heugens, 2019). Our findings suggest differences in IW between the two.…”
Section: Settingmentioning
confidence: 70%
See 1 more Smart Citation
“…Most IW research has been conducted in strong institutions, such as state bureaucracies (Goodstein & Velamuri, 2009;Xiao & Klarin, 2019). Weak institutions are less developed, such as proto-institutions and institutional voids (Gong & Hassink, 2019;Smolka & Heugens, 2019). Our findings suggest differences in IW between the two.…”
Section: Settingmentioning
confidence: 70%
“…Several issues and questions were raised by our findings and framework: (1) Knowledge of IW in proto-institutions and institutional voids remains underexplored (see Gong & Hassink, 2019;Smolka & Heugens, 2019). The same goes for industries not commonly studied with IW theory, such as the creative industries (see Blanc & Huault, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, as suggested by research in the entrepreneurship domain by Cao and Shi (2020), we included peer-reviewed articles and sources from Google Scholar. This allowed us to avoid academic bias (Briner & Denyer, 2012) and was reasoned by the novelty of the bi-directional relationship of INV and home country institutions, which requires further contextualization to reveal their distinctive features and suggest ideas for future empirical research (Greenwood et al, 2017;Smolka et al, 2020). In addition, we found that the responses of INVs to institutional pressures mainly consist of case-base analysis useful for practitioners and government; therefore, such reports were included to fulfil the intention to heed all valuable contributions.…”
Section: Methodsmentioning
confidence: 99%
“…In an uncertain landscape with rapid technological development and government capacity constraints (Smolka & Heu-| 99 gens, 2020), policymakers and regulators demand input from INVs in the process of developing sustainable and favourable legal and normative frames. Therefore, the changing business landscape and shifting institutional arrangements create the need to understand how INVs and policymakers can jointly co-create new regulatory, normative, or cognitive frameworks (Ozcan & Gurses, 2018;Smolka et al, 2020). Thus, to fill this gap, we foreground the following research questions:…”
Section: Introductionmentioning
confidence: 99%
“…The seventh paper is a qualitative paper by Smolka and Heugens (2020). With the lack of a regulatory framework for evaluating new technology‐enabled ventures, they present a process model that reveals how new regulatory structures evolve in the context where high levels of technological and behavioural changes induce systematic uncertainty, and enlarge the interdependence between entrepreneurs and regulators.…”
Section: Articles In This Special Issuementioning
confidence: 99%